2019
DOI: 10.1109/access.2019.2920014
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue EEG Feature Extraction Based on Tasks With Different Physiological States for Ubiquitous Edge Computing

Abstract: Mental fatigue is a gradual and cumulative phenomenon that manifests in the weakening of human physiological activities for ubiquitous edge computing in the Internet of Things. In this paper, two groups of Stroop tasks with different difficulty levels are proposed to induce fatigue, which is evaluated via electroencephalogram (EEG). Wavelet packet decomposition and sample entropy algorithm are utilized to analyze the EEG signals in both sober and fatigue state. The experiment results show that compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…A large body of prior literature has indicated that neurophysiological signals contain information related to physiological state changes, which were acquired via EEG in our experiment ( Lin et al, 2010 ; Xia et al, 2018 ; Asif et al, 2019 ; Monteiro et al, 2019 ; Xu et al, 2019 ; Bajaj et al, 2020 ). Some of the research in recent years has applied machine learning or deep learning methods to identify different stages of physiological states ( Jebelli et al, 2019 ; Ma et al, 2019 ; Khessiba et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of prior literature has indicated that neurophysiological signals contain information related to physiological state changes, which were acquired via EEG in our experiment ( Lin et al, 2010 ; Xia et al, 2018 ; Asif et al, 2019 ; Monteiro et al, 2019 ; Xu et al, 2019 ; Bajaj et al, 2020 ). Some of the research in recent years has applied machine learning or deep learning methods to identify different stages of physiological states ( Jebelli et al, 2019 ; Ma et al, 2019 ; Khessiba et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, EEG power spectra are quantified and divided by frequency ranges, such as delta (1–3 Hz), theta (4–7 Hz), alpha (8–12 Hz), beta (13–31 Hz), and gamma (32–50 Hz) bands ( Tatum, 2014 ), with these oscillations within different frequency bands representative of various brain activations and conditions. Several publications in recent years have appeared documenting that EEG is a robust approach to evaluate physiological states, including alertness, drowsiness ( Lin et al, 2010 ; Bajaj et al, 2020 ), fatigue ( Monteiro et al, 2019 ; Xu et al, 2019 ), and stress ( Xia et al, 2018 ; Asif et al, 2019 ). To assess the changes of physiological states exploiting EEG signals, five parameters are employed to develop the proposed pentagonal physiological state indicator: attention, stress, fatigue, and left and right brain activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Edge computing has become particularly useful in healthcare due to these advantages. Certain illnesses where the usage and benefits of edge computing are evident include Parkinson's disease [21], ECG and EEG feature extraction [22], and chronic obstructive pulmonary disease [23].…”
Section: A Edge Computingmentioning
confidence: 99%
“…One of the most efficient approaches studied within the health sector is through the implementation of new technologies which significantly allowed for the reduction of psychological distress through continuous monitoring of mental state [54]. Electroencephalography (EEG) is one of the most reliable and non-invasive wearable device frequently used in clinical diagnostic tests to measure brain activity such as emotional behaviours, mental fatigue and distraction which are then converted into symptom description [55]. To advance the use of this technology in the construction industry outside of lab settings, a mobile device has been altered and integrated in hardhats to allow continuous monitoring of workforce's mental state [56].…”
Section: Preventative Measuresmentioning
confidence: 99%